The secret of danger point ebook - Dwinell, Kim (Surfside Girls, 2017)
Things are getting weird in Surfside. Lately, Samantha’s best friend Jade explodes into fits of giggles whenever she sees a boy, and it’s throwing a wrench into the kick-back summer of surfing and hanging out that Sam had planned. But after swimming through a secret underwater cave, Sam starts to… see things. Like ghosts. And pirates. And maybe something even scarier! Can she and Jade get to the bottom of this mystery in time to save their town? Author: Kim Dwinell. Illustrator: Kim Dwinell. © 2017 All Rights Reserved.